Stance and strategy: post-structural perspective and post-colonial engagement to develop nursing knowledge - Sochan, Anne M. (Nursing philosophy, 2011)
How should nursing knowledge advance? This exploration contextualizes its evolution past and present. In addressing how it evolved in the past, a probable historical evolution of its development draws on the perspectives of Frank & Gills's World System Theory, Kuhn's treatise on Scientific Revolutions, and Foucault's notions of Discontinuities in scientific knowledge development. By describing plausible scenarios of how nursing knowledge evolved, I create a case for why nursing knowledge developers should adopt a post-structural stance in prioritizing their research agenda(s). Further, by adopting a post-structural stance, I create a case on how nurses can advance their disciplinary knowledge using an engaging post-colonial strategy. Given an interrupted history caused by influence(s) constraining nursing's knowledge development by power structures external, and internal, to nursing, knowledge development can evolve in the future by drawing on post-structural interpretation, and post-colonial strategy. The post-structural writings of Deleuze & Guattari's understanding of ‘Nomadology’ as a subtle means to resist being constrained by existing knowledge development structures, might be a useful stance to understanding the urgency of why nursing knowledge should advance addressing the structural influences on its development. Furthermore, Bhabha's post-colonial elucidation of ‘Hybridity’ as an equally discreet means to change the culture of those constraining structures is an appropriate strategy to enact how nursing knowledge developers can engage with existing power structures, and simultaneously influence that engagement. Taken together, ‘post-structural stance’ and ‘post-colonial strategy’ can refocus nursing scholarship to learn from its past, in order to develop relevant disciplinary knowledge in its future.